Astronomy in Thailand - Busaba Kramer (2018)
During the last few years, Thailand has seen a significant change in the way astronomical research and education is pursued in the country. The government has approved the establishment of the National Astronomical Research Institute of Thailand (NARIT) which aims to develop not only astronomical research but also astronomy education at all levels, both in formal and informal education. A framework of national key projects exists which includes national facilities, national collaborative research networks, teacher training and public outreach programmes. Examples of these programmes will be presented in this paper. © 2007 International Astronomical Union.